Measurement of striated muscle fibre diameters using interactive computer-aided microscopy. Issue 11 (November 1982) - Slavin, G; Sowter, C; Ward, P; Paton, K
Abstract : We have measured muscle fibre diameters using two methods of interactive computer-aided microscopy. They are simple to perform, reproducible and more convenient than manual methods of measurement. The technique is of general application to histological measurement.